2014
DOI: 10.1128/aac.02050-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenemase-Producing Escherichia coli and Klebsiella pneumoniae in the Countries of the Gulf Cooperation Council: Dominance of OXA-48 and NDM Producers

Abstract: pThe molecular epidemiology and mechanisms of resistance of carbapenem-resistant Enterobacteriaceae (CRE) were determined in hospitals in the countries of the Gulf Cooperation Council (GCC), namely, Saudi Arabia, United Arab Emirates, Oman, Qatar, Bahrain, and Kuwait. Isolates were subjected to PCR-based detection of antibiotic-resistant genes and repetitive sequence-based PCR (rep-PCR) assessments of clonality. Sixty-two isolates which screened positive for potential carbapenemase production were assessed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 25 publications
10
105
2
Order By: Relevance
“…The strain was multidrug-resistant, including to carbapenems and colistin, and evolved in the same patient from susceptible to resistant to tigecycline during the course of treatment. A recent study investigating isolates with reduced susceptibility to ertapenem collected from a hospital in Ryiadh between 2011 and 2013 found NDM in one of the two E. coli isolates (Zowawi et al, 2014). The same study reported OXA-48 in 77.5 % of the 40 K. pneumoniae isolates and NDM in 25 %.…”
Section: Carbapenemase Productionmentioning
confidence: 92%
See 2 more Smart Citations
“…The strain was multidrug-resistant, including to carbapenems and colistin, and evolved in the same patient from susceptible to resistant to tigecycline during the course of treatment. A recent study investigating isolates with reduced susceptibility to ertapenem collected from a hospital in Ryiadh between 2011 and 2013 found NDM in one of the two E. coli isolates (Zowawi et al, 2014). The same study reported OXA-48 in 77.5 % of the 40 K. pneumoniae isolates and NDM in 25 %.…”
Section: Carbapenemase Productionmentioning
confidence: 92%
“…The combination of CTX-M and TEM was detected in some isolates, while no other combinations were noted. Recently, CTX-M-15 was reported in all E. coli with reduced susceptibility to ertapenem isolated from Riyadh between 2011 and 2013 (Zowawi et al, 2014).…”
Section: Enterobacteriaceaementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted in Middle East countries also suggests that this region might be an additional reservoir of NDM producers as it has been reported from Oman [13], Lebanon [14], Saudi Arabia [15,16], and Qatar [17].…”
Section: Introductionmentioning
confidence: 83%
“…Molecular detection of carbapenemase genes using polymerase chain reaction (PCR) based methods was found to be quick, accurate and effective in the detection of specific carbapenemases genes, such as KPC, NDM-1, OXA-48, etc. [13][14][15][16][17]. Simple PCR assays targeting a single carbapenemase type have been used successfully in numerous studies.…”
Section: Introductionmentioning
confidence: 99%